2022
DOI: 10.1186/s12951-022-01490-x
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Chinese medicine active ingredients-based selenium nanoparticles regulate antioxidant selenoproteins for spinal cord injury treatment

Abstract: Background As Traditional Chinese Medicine (TCM) drugs, Huangqi and Danshen are always applied in combination for spinal cord injury (SCI) treatment based on the compatibility theory of TCM. Astragalus Polysaccharidesis (APS) and Tanshinone IIA (TSIIA) are the main active ingredients of Huangqi and Danshen, and they both possess neuroprotective effects through antioxidant activities. However, low solubility and poor bioavailability have greatly limited their application. In recent years, seleni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 53 publications
0
42
0
Order By: Relevance
“…A recent study found that AM can inhibit the expression of glial fibrillary acidic protein (GFAP) by increasing SOD activity, thereby preventing or reducing secondary SCI. Moreover, high-dose AM injection can reduce the degree of spinal cord edema and improve spinal nerve function with rat spinal cord injury [ 11 ]. Angelica sinensis (Dang-gui, AS) is the dried root of Angelica sinensis (Oliv.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study found that AM can inhibit the expression of glial fibrillary acidic protein (GFAP) by increasing SOD activity, thereby preventing or reducing secondary SCI. Moreover, high-dose AM injection can reduce the degree of spinal cord edema and improve spinal nerve function with rat spinal cord injury [ 11 ]. Angelica sinensis (Dang-gui, AS) is the dried root of Angelica sinensis (Oliv.…”
Section: Introductionmentioning
confidence: 99%
“…Also, traditional Chinese medicine active ingredients-based SeNPs exhibited protective effects against oxidative stress-induced cytotoxicity in PC12 cells through alleviating mitochondrial dysfunction [ 57 ]. Moreover, MET treatment improved mitochondrial function in leukocytes of PCOS patients [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…15 In addition, selenium plays an essential role as an antibacterial and antioxidant. 16,17 Recently, CoSe 2 was reported as a nanoenzyme with peroxidase (POD) mimicking activity in the detection of glutathione and dye degradation. 18,19 Similarly, a highly specific and sensitive colorimetric test for the detection of H 2 O 2 and glucose was established using CoSe 2 /reduced graphene oxide (CoSe 2 /rGO) nanohybrids, which were revealed to contain intrinsic POD-like catalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to excellent electrocatalytic activity, high availability, environmental friendliness, and structural and compositional advantages, CoSe 2 has attracted considerable attention for its potential to serve as a catalyst for hydrogen peroxide synthesis, hydrogen evolution reaction, oxygen evolution reaction, etc. Cobalt catalysis shares similar reactivity to iron, , which have distinctive electrocatalysis and optical properties, , and are widely used in the battery storage material , and biological medicine. , Selenium is critical to the antioxidant activity of glutathione peroxidase and for cell-protective selenoproteins . In addition, selenium plays an essential role as an antibacterial and antioxidant. , …”
Section: Introductionmentioning
confidence: 99%